Osteoarticular infections in young children: what has changed over the last years? (Swiss Medical Weekly, 2014)
Osteoarticular infections remain a significant cause of morbidity worldwide in young children. They can have a devastating impact with a high rate of serious and long-lasting sequelae, especially on remaining growth. Depending on the localisation of infection, they manifest as osteomyelitis, septic arthritis, a combination of both (i.e., osteomyelitis with adjacent septic arthritis) or spondylodiscitis. Osteoarticular infections can be divided into three types according to the source of infection: haematogenous; secondary to contiguous infection; or secondary to direct inoculation. During the last few years, many principles regarding diagnostic assays and the microbiological causes of these infections have evolved in a significant manner. In the present current-opinion review, we discuss recent concepts regarding epidemiology, physiopathology, and the microbiology of bone and joint infections in young children, as well as clinical presentations, diagnosis, and treatment of these infections. Clinicians caring for children need to be especially well versed in these newer concepts as they can be used to guide evaluation and treatment.